Peranan Kepuasan Kerja Sebagai Variabel Intervening Antara Kompetensi dan Budaya Organisasi Terhadap Kinerja Pegawai Kantor Distrik Navigasi Kelas III Sibolga - Hasugian, Sustih (Universitas Yudharta Pasuruan, 2022)
Abstract English VersionThis study aims to obtain empirical data, facts, and valid and reliable informationabout the influence of organizational culture, competence and learning on employeeperformance, causal studies at the Class III Navigation District Office, Sibolga. This researchwas conducted using a quantitative research approach, using a survey method, carried outfrom January 2022 to March 2022, including pre-survey activities, consolidation, testinginstruments through validity testing and reliability calculations, as well as collecting andprocessing research data. The sample of this research is the entire population that isaffordable, and has the same characteristics, namely as many as 109 state civil servantswith 86 state civil servants in the Sibolga Class III Navigation District Office for the researchsample, which is taken simple randomly, with the number of respondents from all over thearea. state civil servants who meet the research requirements. Measurements in this studywere carried out by giving the value of each question item from all variables, the measure ofthe value given in each statement using the